Designing Large-Scale National and Multi-National Projects in Partnership with National, Regional Partners and IFIs - Ndindeng, S.A.; Manneh, B.; Kouadio, A.L.; Zozo, R.; Ladki, M.; Dadzie, R.; Somado, E.A.; Fregen, M. (2025)
Activity 4.1.2.1 focused on translating proven rice innovation bundles and validated scaling pathways into bankable, large-scale national and multi-national investment projects, co-designed with national governments, regional institutions, and the African Development Bank (AfDB). The activity positioned AfricaRice as a lead technical architect and trusted partner, capable of bridging CGIAR research and scaling evidence with IFI investment requirements to institutionalize impact through sovereign financing. Under this activity, AfricaRice led the full design and negotiation of two multinational rice value chain investment projects, both of which have been approved by AfDB and formalized through signed grant agreements with the African Development Fund. These include the REWARD–Adaptation project, financed under AfDB’s Climate Action Window with a confirmed grant amount of UA 7.11 million, and the Multinational REWARD Program, financed under the African Development Fund with a confirmed grant amount of UA 6.0 million. Together, these two signed agreements represent a total confirmed AfricaRice-led investment envelope of UA 13.11 million, for which AfricaRice serves as Executing Agency and lead technical architect, with responsibility for project design, technical annexes, negotiation, and implementation readiness. In addition to AfricaRice-led investments, the activity delivered significant outcomes through strategic technical assistance to approved national investment programs. AfricaRice provided technical support to the design of REWARD–Gambia, an AfDB-approved national project with an estimated financing envelope of approximately UA 30 million, and to the Economic and Agricultural Value Chain Development Project (EAVCDP) in Angola, an AfDB-approved national investment estimated at approximately USD 200 million. Through this engagement, AfricaRice ensured that rice value chain components were technically robust, climate-resilient, and aligned with proven scaling approaches. The activity also generated a robust pipeline of future large-scale investments, reflecting sustained demand for AfricaRice’s project design leadership. Pipeline operations include REWARD–Ghana (UA 18 million), led by the Government of Ghana and currently under development, as well as two climate-focused technical assistance operations led by AfricaRice under AfDB’s Climate Action Window—one addressing climate change adaptation and greenhouse gas mitigation in rice value chains in West Africa, and another supporting the Climate-Resilient Agri-Food Systems Transformation Programme (CRAFT-1) in South Sudan—with a combined indicative value of approximately USD 2.6 million. Across all approved and pipeline projects, AfricaRice ensured the systematic integration of bundled rice innovation packages, encompassing seed systems, mechanization, post-harvest processing, nutrition-sensitive value addition, climate-smart practices, youth and gender inclusion, and digital tools. By embedding these bundled approaches within sovereign, multi-year investment frameworks, Activity 4.1.2.1 delivered a core CGIAR Scaling for Impact (S4I) outcome: the institutionalization of rice innovation scaling through durable public finance, significantly reducing scaling risk and creating sustained pathways for impact at national and regional levels